'I Can't Keep Up!': an update on advances in soft tissue pathology occurring after the publication of the 2020 World Health Organization classification of soft tissue and bone tumours. Issue 1 (27th December 2021) - Folpe, Andrew L
Abstract : Progress in our understanding of the pathogenesis and diagnosis of soft tissue neoplasia is exceptionally rapid. Although the most recent World Health Organization classification of soft tissue tumours contains many new entities and refinements of older ones, even this comprehensive document is by now incomplete or in need of modification. This review will attempt to summarise the developments in soft tissue pathology that have occurred since 2020, emphasising lesions for which morphology and genetics intersect in a complementary fashion. Novel entities discussed include KMT2A ‐rearranged sarcoma, PRRX :: NCOAx fibroblastic tumours, EWSR1 :: PATZ1 sarcomas, BRAF ‐altered infantile fibrosarcoma‐like lesions, NUTM1 ‐rearranged colorectal sarcomas, and a variety of interesting giant cell‐rich and matrix‐producing lesions. In addition, recently described mimics of atypical lipomatous tumour/well‐differentiated liposarcoma are covered, as is a wholly new, morphologically defined and genetically confirmed entity, pseudoendocrine sarcoma. Finally, exciting new developments in the use of immunohistochemistry as a surrogate for molecular genetic techniques are discussed. Abstract :